Instrucciones para autores (2015)
Revista Colombiana de Bioética (RCB) is spon-sored by the Department of Bioethics at Univer-sidad El Bosque. It is a biannual peer-reviewed publication directed towards academics, resear-chers, academic institutions and professional or-ganizations in Colo